1989
DOI: 10.1056/nejm198904133201501
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1, HIV-2, and HTLV-I Infection in High-Risk Groups in Brazil

Abstract: We conducted a serologic survey for antibodies to human immunodeficiency virus types 1 and 2 (HIV-1 and HIV-2) and human T-cell lymphotropic virus Type I (HTLV-I) in 704 Brazilians with the acquired immunodeficiency syndrome (AIDS) or at risk for it. The study population included 70 homosexual men (11 of whom were prostitutes), 58 bisexual men (19 of whom were prostitutes), 101 female prostitutes from three socioeconomic groups, 13 wives of men with hemophilia who were seropositive for HIV-1 antibodies, and 47… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0
7

Year Published

1990
1990
1999
1999

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(44 citation statements)
references
References 25 publications
0
37
0
7
Order By: Relevance
“…Cortes et al 4 in a serologic screening among AIDS high risk patients also investigated HTLV-l antibodies, detected chiefly in hemophiliac patients; SP is not mentioned. Castro et al3 studied 16 cases with SP and 13 MS cases with spinal cord involvement; HTLV-l serumpositivity was detected in 6 SP patients and in one MS case.…”
Section: Commentsmentioning
confidence: 99%
“…Cortes et al 4 in a serologic screening among AIDS high risk patients also investigated HTLV-l antibodies, detected chiefly in hemophiliac patients; SP is not mentioned. Castro et al3 studied 16 cases with SP and 13 MS cases with spinal cord involvement; HTLV-l serumpositivity was detected in 6 SP patients and in one MS case.…”
Section: Commentsmentioning
confidence: 99%
“…A person's sexual orientation determines, in part, the type of sexual acts that person is willing to engage in and the partners with whom that person has sex.6 9 The HIV rates were significantly higher among the homosexually and bisexually oriented prostitutes, who were also more likely to engage in receptive anal intercourse than were their heterosexually oriented peers. While the data initially indicated a relationship between HIV infection and sexual orientation, these bivariate relationships were nonsignificant once a measure of receptive anal sex with either a paying or a nonpaying partner was evaluated simultaneously in the multivariate model.…”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3][4] Although considerably less is known about male prostitution,5-' the emphasis on females has led researchers to neglect the possible importance of their male counterparts in transmitting human immunodeficiency virus (HIV) and other sexually transmitted diseases into heterosexual, homosexual, and bisexual populations. HIV studies of male prostitutes have been of limited scope, 8,9 have been conducted largely in institutional settings, or have involved self-report of HIV status.71'0 Male prostitutes engage in several identified high-risk behaviors for sexually transmitted disease and HIV. For example, they have multiple paying and nonpaying sex partners whom they have little opportunity to screen, they engage in sexual behaviors that place them at high risk for HIV,7 they have high rates of sexually transmitted disease,4,6,11 and they are often intravenous drug users.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the great number of AIDS cases in Brazil 18 and the high prevalence of HIV 5,19 no studies have been found on the influence of an HIV positive status on sexual behavior in the country.…”
Section: Introductionmentioning
confidence: 99%